2009
DOI: 10.1590/s0103-84782009005000152
|View full text |Cite
|
Sign up to set email alerts
|

Comprimento da estaca no desenvolvimento de mudas de alecrim-pimenta

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
2
5
0
5
Order By: Relevance
“…The values with and without leaf area reduction were 9.79 and 8.57 cm, respectively. The largest cuttings reached greater heights (Table 2) in agreement with what was observed by Carvalho Júnior et al [14]. However, considering that all the cuttings were planted 2 cm deep in the substrate, when analyzing the increase in height, it was observed that the seedlings produced from the smaller cuttings exhibited greater vitality; that is, they grew to 5.50, 4.45, 3.90, and 2.87 cm for S treatments of 4, 6, 8, and 10 cm, respectively.…”
Section: Resultssupporting
confidence: 91%
“…The values with and without leaf area reduction were 9.79 and 8.57 cm, respectively. The largest cuttings reached greater heights (Table 2) in agreement with what was observed by Carvalho Júnior et al [14]. However, considering that all the cuttings were planted 2 cm deep in the substrate, when analyzing the increase in height, it was observed that the seedlings produced from the smaller cuttings exhibited greater vitality; that is, they grew to 5.50, 4.45, 3.90, and 2.87 cm for S treatments of 4, 6, 8, and 10 cm, respectively.…”
Section: Resultssupporting
confidence: 91%
“…The total number of shoots were evaluated on the autumn, considering their development occurred during the seedling formation (40 days). The number of shoots per Research, Society andDevelopment, v. 9, n. 10, e8489109196, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.9196 cutting was adjusted to the growing linear model (Figure 4 A) according to the increase in cutting size, comparable to the results of Biase & Costa (2003) when analyzing different cuttings sizes of Lippia alba and that of Carvalho Junior, et al (2009) with Lippia sinoides cuttings. This can probably be attributed to the greater number of axillary buds and the greater quantity of reserves present in piles of greater length.…”
Section: Resultssupporting
confidence: 59%
“…Moreover, a quality root system improves the water and nutrient absorption in the early development stages. A greater root length and a large number of roots are important in the large-scale seedling production, since these parameters are vital to a successful implementation in the field (Carvalho Júnior et al 2009). e-ISSN 1983-4063 -www.agro.ufg.br/pat -Pesq.…”
Section: Resultsmentioning
confidence: 99%